Gated Detection Measurements of Phosphorescence Lifetimes - Yordan Kostov; Govind Rao (Bioautomation, 2004)
A low-cost, gated system for measurements of phosphorescence lifetimes is presented. An extensive description of the system operating principles and metrological characteristics is given. Remarkably, the system operates without optical filtering of the LED excitation source. A description of a practical system is also given and its performance is discussed. Because the device effectively suppresses high-level background fluorescence and scattered light, it is expected to find wide-spread application in bioprocess, environmental and biomedical fields.